Sophisticated and self-regulated microcapsules compartmentalizing cells and microparticles for tissue regeneration - Santos, Sara Nadine (2023)
Traditional tissue engineering devices commonly neglect the immune system's role in regulating tissue dynamics. Consequently, inconsistencies between in vitro and in vivo studies are frequently reported. Furthermore, the lack of diffusion of essential molecules for cell survival and signalling dictates the failure of most 3D bioengineered strategies upon implantation. The present thesis proposes a liquefied cell-encapsulation approach with immunomodulatory properties designed to regenerate damaged tissues. The 3D liquefied capsules are composed of: (i) a permselective membrane wrapping the core content while fully addressing the exchange efficiency of biomolecules; (ii) surface-functionalized poly(-caprolactone) microparticles that act as cell adhesion domains for anchorage-dependent cells; and (iii) stem/stromal cells. Multi-shaped liquefied capsules with high geometrical precision and efficiency were generated to mimic the complexity of native tissues. The potential of liquefied capsules as an immunomodulatory 3D platform was also validated for the in vitro combinatorial screening of different biomaterials and cells. The last layer of the liquefied capsules, as well as the encapsulation of stem/stromal cells, influence the external immune ecosystem. When applied to bone tissue engineering, the proposed cell-encapsulation system was successful in engineering bone-like mineralized microtissues. To overcome the size limitation of liquefied capsules and increase their injectability, miniaturized microcapsules were generated by electrohydrodynamic atomization. The microcapsules were cultured under a dynamic environment utilizing spinner flasks to simulate the native bone tissue. The advantage of the unique confined liquefied core microenvironment is the enhanced interactions between cells, leading to the direct development of bone-like aggregates even in the absence of osteoinductive factors. Taking inspiration from the multiphenotypic cellular environment of bone tissue, human umbilical cord-derived cells, namely macrophages, mesenchymal-derived stromal cells, and endothelial cells, were co-cultured within the liquefied microcapsules. The biomolecular interactions inside the microcapsules increased stem/stromal cells’ osteogenesis and angiogenesis, emphasizing the vital role of macrophages in regulating bone dynamics. The use of the umbilical cord-derived cells determined the ability of the microcapsules for personalized cell therapies. Altogether, the proposed bioencapsulation strategy is a powerful self-regulated system, which might find great applicability in bone tissue engineering based on bottom-up approaches or disease modelling.